ChemInform Abstract: Cyclopropanation of 1, 2‐Dibromoethylphosphonate: A Synthesis of β‐Aminocyclopropylphosphonic Acid and Derivatives. Issue 15 (April 2015) - Rabasso, Nicolas; Fadel, Antoine
Abstract: The reaction of phosphonate (I) with nitroalkanes gives cyclopropanes with exclusive trans‐selectivity.